Kenyan awareness of aflatoxin: An analysis of processed milk consumers - Mtimet, Nadhem; Walke, M.; Baker, Derek; Lindahl, Johanna F.; Hartmann, M.; Grace, Delia (2015)
Aflatoxin is a human health threat in many developing countries. This study examines Kenyan milk consumers’ behaviour toward aflatoxin by way of choice experiments. Further, the willingness to pay for different types of milk and aflatoxin status awareness was assessed. Five attributes were selected to describe milk products: milk processing technique, fat content, packaging, price and aflatoxin-free certification. Results indicate that awareness of aflatoxin is high, and that consumers are willing to pay a significant premium for milk that is certified as aflatoxin-free. Results also show, however, that the substantial majority does not know how to avoid aflatoxin-contaminated milk. The results indicate a great need for further education and awareness-raising programs throughout the Kenyan dairy value chain, and a potential for market-based solutions to aflatoxin control in milk.